Cerebral cortex maldevelopment in syndromic craniosynostosis. (15th July 2021) - Wilson, Alexander T; Den Ottelander, Bianca K; Van Veelen, Marie‐Lise C; Dremmen, Marjolein HG; Persing, John A; Vrooman, Henri A; Mathijssen, Irene MJ; Tasker, Robert C
Abstract : Aim: To assess the relationship of surface area of the cerebral cortex to intracranial volume (ICV) in syndromic craniosynostosis. Method: Records of 140 patients (64 males, 76 females; mean age 8y 6mo [SD 5y 6mo], range 1y 2mo–24y 2mo) with syndromic craniosynostosis were reviewed to include clinical and imaging data. Two hundred and three total magnetic resonance imaging (MRI) scans were evaluated in this study (148 patients with fibroblast growth factor receptor [ FGFR ], 19 patients with TWIST1, and 36 controls). MRIs were processed via FreeSurfer pipeline to determine total ICV and cortical surface area (CSA). Scaling coefficients were calculated from log‐transformed data via mixed regression to account for multiple measurements, sex, syndrome, and age. Educational outcomes were reported by syndrome. Results: Mean ICV was greater in patients with FGFR (1519cm 3, SD 269cm 3, p= 0.016) than in patients with TWIST1 (1304cm 3, SD 145cm 3 ) or controls (1405cm 3, SD 158cm 3 ). CSA was related to ICV by a scaling law with an exponent of 0.68 (95% confidence interval [CI] 0.61–0.76) in patients with FGFR compared to 0.81 (95% CI 0.50–1.12) in patients with TWIST1 and 0.77 (95% CI 0.61–0.93) in controls. Lobar analysis revealed reduced scaling in the parietal (0.50, 95% CI 0.42–0.59) and occipital (0.67, 95% CI 0.54–0.80) lobes of patients with FGFR compared with controls. Modified learning environments were needed more often in patients with FGFR . Interpretation: Despite adequate ICV in FGFR ‐mediated craniosynostosis, CSA development is reduced, indicating maldevelopment, particularly in parietal and occipital lobes. Modified education is also more common in patients with FGFR .